2021
DOI: 10.1039/d1dt02565a
|View full text |Cite
|
Sign up to set email alerts
|

PhICl2 is activated by chloride ions

Abstract: A study on the potential activating role of pyridine in the electrophilic chlorination of anisole by PhICl2 has led to the discovery that soluble sources of chloride ions activate PhICl2...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…5,6 On standing in solution or at room temperature, PhICl 2 degrades into PhI and Cl 2 , which in solution occurs over a matter of hours. 7 PhIF 2 and related derivatives (most often with tolyl as the aryl group) are commonly used as a fluorinating agents. [8][9][10] PhIF 2 derivatives are somewhat less convenient to synthesize compared to PhICl 2 , and are also reactive with borosilicate glass.…”
mentioning
confidence: 99%
“…5,6 On standing in solution or at room temperature, PhICl 2 degrades into PhI and Cl 2 , which in solution occurs over a matter of hours. 7 PhIF 2 and related derivatives (most often with tolyl as the aryl group) are commonly used as a fluorinating agents. [8][9][10] PhIF 2 derivatives are somewhat less convenient to synthesize compared to PhICl 2 , and are also reactive with borosilicate glass.…”
mentioning
confidence: 99%
“…3 Addition of chloride ions was found to effectively catalyze the release of Cl 2 from PhICl 2 via an as-yet undetermined mechanism. 4…”
Section: Introductionmentioning
confidence: 99%
“…11 NO 2 –C 6 H 4 –I(OTf) 2 proved to be highly reactive, capable of performing transformations that other ArIL 2 species are incapable of, including the oxidation of cyclohexenes to aromatic rings and direct sp 3 C–H and C–F functionalization. 12 We hypothesized that use of an even more weakly coordinating ligand could further enhance the potential reactivity of the I( iii ) and targeted using bistriflimide (NTf 2 ) as the ligand as the next step. While we were undertaking this study Periana and co-workers isolated and spectroscopically characterized C 6 F 5 –I(NTf 2 ) 2 and showed that at elevated temperatures and pressures direct C–H activation of simple alkanes is possible.…”
mentioning
confidence: 99%
“…The most remarkable reaction observed thus far is the rapid, low temperature oxidation of cyclohexene rings into aryls. 12 NO 2 –C 6 H 4 –I(OTf) 2 can oxidize terpenes to p -cymene, a relatively facile oxidation, but also cyclohexene itself to benzene in a 4-electron oxidation using 2 equivalents of NO 2 –C 6 H 4 –I(OTf) 2 . While benzene is a trivial compound, this direct oxidation typically requires high temperatures, long reaction times and a Pd oxide catalyst using molecular O 2 as the oxidant.…”
mentioning
confidence: 99%
See 1 more Smart Citation